2006
DOI: 10.1111/j.1532-5415.2005.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density Testing in Older Women and Its Association with Patient Age

Abstract: In the 3 years after Medicare reimbursement for osteoporosis screening began, adoption of bone density testing was lowest in women in age groups at highest fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…[1][2][3]26,27 These findings may have some legitimate explanations. Black and Hispanic women have a lower incidence of hip fracture and likely fewer fracture risk factors, and the predictive ability of BMD testing in these groups is not as well-studied as in white women.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[1][2][3]26,27 These findings may have some legitimate explanations. Black and Hispanic women have a lower incidence of hip fracture and likely fewer fracture risk factors, and the predictive ability of BMD testing in these groups is not as well-studied as in white women.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have found 20-50% lower use of bone density screening for black women, and 23% less testing for Hispanic women. [1][2][3] Racial differences in screening are generally interpreted as indicators of poorer quality of care. 4 However, there are possible legitimate explanations for racial differences in osteoporosis screening among women who have not had a fracture.…”
Section: Introductionmentioning
confidence: 99%
“…2 Patient and provider factors contribute to failure to participate in screening, 3 and obtaining a DXA may be inconvenient if it requires a separate clinic appointment or a physician referral. This may be problematic for older women or women with multiple comorbidities, who are less likely to receive a DXA, 3,4 suggesting that more innovative methods may be required to reach them. The purpose of this study was to develop and pilot test a novel approach to screening high-risk women for osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Current osteoporosis treatment decisions do not correlate well with objective measures of patient fracture risk. Specifically, osteoporosis appears to be underrecognized and under-treated in older patients (5,6), patients with multiple osteoporosis risk factors (7), and patients with prior fractures (8)(9)(10). It is not known whether there is widespread treatment of lower-risk patients, but by one estimate nearly 13% of women over 65 are receiving osteoporosis treatment (11).…”
Section: Introductionmentioning
confidence: 99%